THE EFFECT OF SEA CUCUMBER (HOLOTHURIA SCABRA) EXTRACT AS HEPATOPROTECTIVE: HISTOPATHOLOGICAL STUDY - Abdulkadir, Widy Susanti; Tungadi, Robert (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Sea cucumber Holothuria scabra is one of the marine animals that can be consumed as food and also efficacious as a drug. One of the benefits of sea cucumber has high cell regeneration ability. This study aims to see the profile of hepatoprotective histology of sea cucumber extract on mice that have been given paracetamol toxic dose. Methods: This experiment was conducted using experimental animal grouped of mice which were divided into six groups: Group I: sea cucumber extract 1%, Group II: 1000 mg/kg body weight (BW) or 25 mg/25 g BW, Group III: 750 mg/kg BW or 18.75 mg/25 g BW, Group IV: 500 mg/kg BW or 12.5 mg/25 g BW, Group V: positive control (curcuma tablet 2.5 mg/25 g BW), and Group VI: paracetamol group (62,5 mg/25 g BW). The histopathology test was performed to see the improvement of liver necrosis of mice. Results: The results of histopathological study showed that all groups of mice livers experienced necrosis (cell damage) and abnormalities. In the group of sea cucumber extract having dose 500 mg/kg BW, liver cells experienced degeneration of fat and hemorrhage as in the group of curcuma tablet, but in Group VI (paracetamol group), liver of mice experienced apoptosis (cell death). In the histopathology test, results can also be seen that in Group IV at doses of 500 mg/kg BW, the liver experienced slightly less severity than all other groups. Conclusion: The sea cucumber at doses of 500 mg/kg BW can improve the hepatic damage on mice induced by paracetamol.